Association of Hamstring Flexibility and Skills Performance among Collegiate Recreational Futsal Players in Subang Jaya, Malaysia - Yap, Colin, Yew Chuen; Vinodhkumar, Ramalingam; Viswanath, Sundar (INTI International University, 2020)
Background: Muscle flexibility is one of the most vital aspects of fitness and health that plays an important role in the human body functions. In sports such as futsal, lower limb musculature has its principle function that the properties of these muscles influence performance and skills within the sport. The specific performance traits such as speed, power, and endurance were widely studied however, the specific skills and attributes of futsal sports pass accuracy, ball control, trapping, reflex, consistency, and agility in association with hamstring flexibility were not much reported. Objective: This study aims to find the association between hamstring flexibility and skills performance of collegiate recreational futsal players. Methodology: This study includes 100 volunteered male collegiate recreational futsal players with ages range18-25 years. The participants' hamstring flexibility was tested by using V-sit and reach test and the futsal skills performance with the McDonald soccer skill test. The data were analyzed statistically to find the association using Pearson’s Correlation and Linear regression. Results: The participants showed a strong association between hamstring flexibility and futsal skill performance with r = 0.701, p= <0.001. Linear regression analysis showed a strong association and predictor value for hamstring flexibility as a factor for futsal skills performance scores with r^2 = 0.492. Conclusion: The study concludes hamstring flexibility is an integral part and plays a major role in the betterment of futsal skills performances unique to the specific game, besides it pivotal in maintaining performance and reducing the risk of injuries among players.